Desempenho agronômico de híbridos de milho associado ao uso de fungicida em anos de La Niña - Schlösser, Onássis Deivis (2023)
Corn (Zea mays L.) is the most produced grain in the world. With the intensification of management and the increase in the cultivation area, the need for the use of preventive fungicides in maize crops is frequent. In this sense, the objective of this work was to evaluate the agronomic performance of corn hybrids, associated with the use of preventive fungicide and measurement of helminthosporiose severity, by diagrammatic scale, in subtropical environments in southern Brazil in years of the La Niña phenomenon. The present study was conducted in the 2020/2021 and 2021/2022 harvests in the municipality of Santa Maria - RS (SM1 and SM2) and in 2021/2022 in São Vicente do Sul - RS (SVS). The design used was a 2 x 8 factorial, the treatments consisted of eight corn hybrids with and without application of fungicide. Fertilization was carried out with the aid of a five-line seeder, spaced 0.5m apart. Sowing was carried out manually, with density adjusted to 70,000 plants ha-1. The genetic resistance of the hybrids and the low pressure of fungal inoculum in the cultivation area, associated with the La Niña phenomenon that provided low volumes of precipitation and low air humidity during the crop cycle, provide fewer hours of leaf wetness for the crop. Consequently, these factors were unfavorable for the development of foliar diseases, with low incidence and severity of disease in corn. The management of fungicides in corn hybrids, aiming at a significant increase in grain yield, should be recommended with caution, especially if there is low expectation of grain yield in years with low rainfall. Helminthosporiose severity assessments are essential for disease quantification, where regardless of the digital method or diagrammatic scale, which results in better accuracy and precision in the estimates made, these tools being easy and quick to use, which can be adopted to assist in the evaluation of helminthosporiosis severity in maize.